Helical 1:1 α/Sulfono-γ-AA Heterogeneous Peptides with Antibacterial Activity - She, Fengyu (Biomacromolecules, 2016)
As one of the greatest threats facing the 21st century, antibiotic resistance is now a major public health concern. Host-defense peptides (HDPs) offer an alternative approach to combat emerging multi-drug-resistant bacteria. It is known that helical HDPs such as magainin 2 and its analogs adopt cationic amphipathic conformations upon interaction with bacterial membranes, leading to membrane disruption and subsequent bacterial cell death. We have previously shown that amphipathic sulfono-γ-AApeptides could mimic magainin 2 and exhibit bactericidal activity. In this article, we demonstrate for the first time that amphipathic helical 1:1 α/sulfono-γ-AA heterogeneous peptides, in which regular amino acids and sulfono-γ-AApeptide building blocks are alternatively present in a 1:1 pattern, display potent antibacterial activity against both Gram-positive and Gram-negative bacterial pathogens. Small angle X-ray scattering (SAXS) suggests that the lead sequences adopt defined helical structures. The subsequent studies including fluorescence microscopy and time-kill experiments indicate that these hybrid peptides exert antimicrobial activity by mimicking the mechanism of HDPs. Our findings may lead to the development of HDP-mimicking antimicrobial peptidomimetics that combat drug-resistant bacterial pathogens. In addition, our results also demonstrate the effective design of a new class of helical foldamer, which could be employed to interrogate other important biological targets such as protein–protein interactions in the future.